2011
DOI: 10.1111/j.1365-2265.2010.03955.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone geometry and volumetric bone mineral density in girls with Turner syndrome of different pubertal stages

Abstract: There is a cortical bone deficit in girls with TS characterized by low cortical area, thin cortex and probably decreased cortical vBMD. Early commencement of GH therapy, as well as oestrogen replacement, is associated with higher cortical vBMD. Further studies should investigate the potential causality of this relation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 31 publications
3
40
1
Order By: Relevance
“…This hypothesis owes to studies reporting lower aBMD of the one-third distal radius opposed to the ultradistal radius using DXA, (8,35) and lower cortical vBMD and/or cortical thickness in the proximal radius using pQCT. (18)(19)(20) Our results do not support the hypothesis of a selective cortical bone deficit in TS. On the contrary, TS patients in our study had compromised trabecular integrity in both radius and tibia, with significantly lower trabecular BV/TV and higher trabecular spacing.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…This hypothesis owes to studies reporting lower aBMD of the one-third distal radius opposed to the ultradistal radius using DXA, (8,35) and lower cortical vBMD and/or cortical thickness in the proximal radius using pQCT. (18)(19)(20) Our results do not support the hypothesis of a selective cortical bone deficit in TS. On the contrary, TS patients in our study had compromised trabecular integrity in both radius and tibia, with significantly lower trabecular BV/TV and higher trabecular spacing.…”
Section: Discussioncontrasting
confidence: 95%
“…Also, measurement of cortical vBMD by pQCT is influenced by cortical thickness, due to partial volume artifacts, resulting in falsely low values in thin compared to thicker cortices. (38) Correspondingly, Soucek and colleagues (20) reported that when proximal radius cortical vBMD in TS patients was adjusted for partial volume artifacts, cortical vBMD rose from below normal to above normal reference values. Third, TS patients in our study were older (median age 35 years) compared to previous studies using pQCT (age range 6-25 years (18)(19)(20) ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the vBMD findings observed in group S, which were significantly greater than those in group E, may indicate that estrogen administration in group E should have been started earlier than done in this study in order to achieve adequate BMD in patients with TS who are not expected to experience regular menstruation. One of our previous studies reported a decrease in actual BMD as measured by quantitative computed tomography in TS patients not only during, but also before puberty [21], as well as in other groups [22,23].…”
Section: Fig 2 Volumetric Bmd (Vbmd) In the 3 Groups (E L And S)mentioning
confidence: 99%